2004
DOI: 10.2306/scienceasia1513-1874.2004.30.255
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT:The distribution of arsenic in roots and edible parts of Ipomoea reptans in presence of phosphate fertilizer was assessed in a pot experiment in Khulna, Bangladesh. There were 9 treatments with the combination of 3 levels of arsenic (0, 2 and 30 mg kg -1 soil) and 3 levels of phosphorus (0, 40 and 80 mg kg -1 soil). The study was carried out in a 3x3 factorial experiment with three replicates using completely randomized design. Arsenic application in soils significantly increased its accumulation in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Besides, high consumption of vegetables and fruit has been recognized to positively correlate with decreased risk of chronic and nondegenerative diseases, such as cardiovascular disease, cancer, and diabetes mellitus (Carter et al, 2010;van't Veer et al, 2000). A and C and essential minerals such as calcium and iron (Dewanjee et al, 2015;Rahman & Parkpain, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, high consumption of vegetables and fruit has been recognized to positively correlate with decreased risk of chronic and nondegenerative diseases, such as cardiovascular disease, cancer, and diabetes mellitus (Carter et al, 2010;van't Veer et al, 2000). A and C and essential minerals such as calcium and iron (Dewanjee et al, 2015;Rahman & Parkpain, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The primary hazard of cigarette smoking (either voluntarily or involuntarily) is oxidative stress, and it is suggested that reactive oxygen species (ROS) in the smoke is the culprit. , ROS in smoke includes peroxyl radicals, carbon-centered radicals, and nitric dioxides . Evidence has shown that ROS can damage DNA, initiate lipid peroxidation, and cause inflammation.…”
mentioning
confidence: 99%